Process and Outcomes of a Skin Protection Intervention for Young Adults - Heckman, Carolyn J. (2012)
BACKGROUND: Efforts to reduce skin cancer risk behaviors using appearance-oriented interventions (e.g., ultraviolet [UV] light photos showing skin damage) or Motivational Interviewing (MI) have shown promise in recent trials. METHOD: A randomized 2 (UV photo versus no UV photo) × 2 (MI versus no MI) factorial design with longitudinal follow up. RESULTS: Progression in stage of change (SOC) was significantly more likely in the photo than the education condition. Treatment credibility as rated by participants and counselor perceived positive therapeutic alliance predicted SOC progression. There was also preliminary evidence for differential intervention effectiveness by baseline SOC. CONCLUSIONS: Implications are discussed.